The strategic alliance of higher education institutions: Experience of contemporary Germany - A. M. Petrov (Образование и наука)
Introduction. In the context of current trends in the development of the modern world, the successful solution of numerous socio-economic problems is possible only on the condition of effective functioning of higher education system, in which higher education institutions do not only implement the mission of providing society with high-quality and relevant educational services, but also carry out research and development of entrepreneurial nature. In this regard, search for opportunities to fulfill such missions currently takes precedence. The formation of alliances between higher education institutions can be considered as one of the promising mechanisms for performing such missions, as well as for integrative solution of issues in the field of public policy to support and develop higher education. In Russia, insufficient attention is paid to the issues of alliance formation within the sphere of higher education. Therefore, it is relevant to analyse foreign practices, i.e. a specific strategic alliance by higher educational institutions in Germany - The Berlin University Alliance.The aim of the present work is to contribute to the evidence base of research in the field of development of strategic cooperation between higher educational institutions, as well as to define the prospects for alliance formation through the analysis of foreign practices.Methodology and research methods. The methodological framework involves the following general scientific methods: systematisation and generalisation, structural and functional analysis, comparative and retrospective analysis of data from international rankings. The study was based on materials presented on the official Internet resources of “The Berlin University Alliance”, German programme “The Excellence Strategy”, international ranking agencies QS and THE, as well as scientific publications included in international citation databases Web of Science (RSCI) and Scopus.Results and scientific novelty. Based on established research, theoretical approaches to understanding the essence of alliances were structured; the criteria for classification of alliances were defined; the possibilities of alliances and factors, which serve as prerequisites for their formation, were investigated. The novelty of the current research lies in the fact that the author presents his own opinion on the phenomena in relation to such categories as “university alliance”, “strategic partnership” and “alliance formation”. Moreover, the author reports on the results obtained in the course of the analysis of the Berlin University Alliance as an example of the development of strategic partnership between higher education institutions in Germany.Practical significance. The present research may be a useful guideline for forming alliances between higher education institutions and generating new ideas for its development. The research outcomes can be used not only by the leaders of higher education institutions, but also by the experts and specialists involved in forming and implementing state policy in the field of higher education development.